Transcutaneous Electrical Acupoint Stimulation Combined with Moderate Sedation of Remimazolam Tosilate in Gastrointestinal Endoscopy: A Prospective, Randomized, Double-Blind, Placebo-Controlled Clinical Trial - Jian-Han Xu; Hai-Ling Tan; Li-Na Zhang; Zan-Gong Zhou; Li Yuan; Ling-Xin Kong; Ming-Quan Song; Li-Jie Qi; Xiang-Yu Ji (Pain and Therapy, 2024)
Abstract Introduction Further clinical validation is required to determine whether transcutaneous electrical acupoint stimulation (TEAS) can replace opioids and be used in combination with remimazolam for sedation during gastrointestinal endoscopy. Methods A total of 108 outpatients who underwent diagnostic gastrointestinal endoscopy were randomly divided into three groups: fentanyl plus remimazolam group (group C), TEAS plus remimazolam group (group E), and placebo-TEAS plus remimazolam group (group P). The assessments of patient satisfaction, physician satisfaction, and pain scale score during the examination constituted the primary endpoints of the study. The secondary endpoints were the time of recovery, recovery of normal behavioral function and discharge, incidence of adverse reactions, and dose of remimazolam. Results Compared with group C, group E had a greater median score for patient satisfaction at follow-up and a slightly lower median score for physician satisfaction. The pain score of group E was slightly greater than that of group C, but the difference was not significant. However, in group C, the incidence of hypoxemia, the rate of nausea and the severity of vertigo were greater, and the number of patients discharged and resuming normal behavioral function was greater than those in the other two groups. The dose of remimazolam in group C and group E was less than that in group P. Conclusions TEAS combined with moderate sedation of remimazolam can provide an ideal sedative effect, which preferably suppresses discomfort caused by gastrointestinal endoscopy and has fewer sedation-related complications. Trial Registration ID: NCT05485064; First registration (29/07/2022); Last registration (02/11/2022) (Clinical Trials.gov).